Nexus between corporate governance practices and cost of capital in PSX listed firms - Muhammad Arslan; Sazali Abidin (Cogent Economics & Finance, 2019)
The aim of this study is to examine the relationship between corporate governance (CG), in terms of its internal significance, and cost of capital (COC), based on a sample of listed firms of Pakistan Stock Exchange (PSX) over the period of 2009-2015. We used Pakistan as a case study mainly because we expect that key features of Pakistani setting in terms of CG and financial markets will have impact on the relationship between CG and COC. Drawing on a sample of 120 PSX listed firms, we find that CG compliance and disclosure (CG index [CGI]) has improved over time among PSX listed firms. The findings also reveal a positive relationship of institutional, government and director ownership with both CGI and COC, while this relationship becomes negative with block ownership. The findings of 2SLS reveal a significant negative association between CG compliance and COC; hence, firms with higher CG score enjoy a lower COC. Interestingly, gender diversity and board size have a negative association with CG compliance and COC, while audit firm size reveals a positive association with CG compliance and disclosure while a negative association with COC. The study contributes to existing literature dealing with CG and determinant of firm value (COC) in emerging markets, particularly in Pakistan, which has not been extensively explored in existing research.
Keywords: 330; Corporate governance; compliance and disclosure; cost of capital; 2SLS; ownership structure; PSX